2017
DOI: 10.1016/j.bbrep.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

On mechanism of antioxidant effect of fullerenols

Abstract: Fullerenols are nanosized water-soluble polyhydroxylated derivatives of fullerenes, specific allotropic form of carbon, bioactive compounds and perspective pharmaceutical agents. Antioxidant activity of fullerenols was studied in model solutions of organic and inorganic toxicants of oxidative type – 1,4-benzoquinone and potassium ferricyanide. Two fullerenol preparations were tested: С60О2–4(ОН)20–24 and mixture of two types of fullerenols С60О2–4(ОН)20–24+С70О2–4(ОН)20–24. Bacteria-based and enzyme-based biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 64 publications
(77 reference statements)
1
36
1
Order By: Relevance
“…(abiotic stressors), reflect on the reactive oxygen species, and more specifically, the signals (nuclear factors) that initiate/modulate biosynthesis of secondary metabolites, if the stressor is within the level that induces adaptation and survival rather than cell death [10,28,29]. At the same time, fullerol C 60 (OH) 24 nanoparticles (FNP) possess an antioxidative potential and poorly defined environmental reactivity [10,12,30]. These factors suggest that FNP modulation of the secondary metabolite profile of mycotoxigenic fungi would likely add to already increased contamination of the environment by mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…(abiotic stressors), reflect on the reactive oxygen species, and more specifically, the signals (nuclear factors) that initiate/modulate biosynthesis of secondary metabolites, if the stressor is within the level that induces adaptation and survival rather than cell death [10,28,29]. At the same time, fullerol C 60 (OH) 24 nanoparticles (FNP) possess an antioxidative potential and poorly defined environmental reactivity [10,12,30]. These factors suggest that FNP modulation of the secondary metabolite profile of mycotoxigenic fungi would likely add to already increased contamination of the environment by mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 11. Antioxidant activity of humic substances was studied in [80][81][82][83][84] and fullerenols -in [84][85][86][87]. Cellular and enzymatic assays were used to evaluate a General Toxicity (GT) under conditions of the oxidative stress; this stress was modeled in the solutions of exogenous organic or inorganic oxidizers (1,4-benzoquinone or potassium ferricianide, respectively).…”
Section: Luminescence Bioassays As Tools For Study Low-dose Radiationmentioning
confidence: 99%
“…The latter appears in the presence of Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 21 August 2019 doi:10.20944/preprints201908.0221.v1exogenous oxidizers, depending on their redox potential and concentration[25]. Justification for GTand OxT application to evaluate toxicity of bioactive compounds is presented in[80][81][82][83][84][85][86][87].Principle of antioxidant efficiency evaluation is presented inFigure forbacteria-based (upper line) and enzyme-based (lower line) bioassays; humic substances are chosen here as an example of an antioxidant agent.…”
mentioning
confidence: 99%
“…Fullerenols are bioactive compounds, polyhydroxylated water-soluble derivatives of fullerenes, a third natural allotropic variation of carbon [5,16,17]. The chemical structure of fullerenol C 60 (OH) x is presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study carried out by Yin et al (2009) [22] indicated that C 60 (C(COOH) 2 ) 2 , C 60 (OH) 22 , and Gd@C 82 (OH) 22 could protect cells against H 2 O 2 -induced oxidative damage, stabilized the mitochondrial membrane potential, and reduced intracellular ROS production. Due to their hydrophilic properties and the ability to scavenge free radicals, fullerenol could provide a valuable alternative to conventional pharmacological agents [17]. The effect of polyhydroxylated fullerenol NPs on adult male Wistar rats treated with DOX was investigated by Jacevic et al (2017) [23].…”
Section: Introductionmentioning
confidence: 99%